Pemaksimalan Fungsi Penanaman Mangrove di Daerah Rawan Abrasi Jakarta - Ardhi Prasetyo Utomo; Jamilah Okta Haerani; Rio Nur Ferdian; Risqika Paradise; Denny Oktavina Radianto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Planting mangroves along the coast of Jakarta is an important strategy in addressing coastal erosion and preserving environmental sustainability. Mangroves, with their strong roots and efficient water absorption system, help mitigate coastal erosion and strengthen coastal structures. Amidst rapid population growth and infrastructure development, the risk of coastal erosion increases, influenced by global climate change. Research shows significant economic losses due to coastal erosion, threatening the preservation of coastal ecosystems and human settlements. Planting mangroves provides benefits in combating coastal erosion. In addition to coastal protection, mangroves enhance biodiversity, sequester carbon, restore degraded land, and empower local communities through ecotourism and sustainable natural resources. Implementation requires careful planning and collaboration among government, communities, and non-governmental organizations. With the natural protection provided by mangroves, the risk of coastal erosion can be reduced, coastal infrastructure can be maintained, and the sustainability of coastal ecosystems preserved. Mangrove planting should be an integral part of coastal erosion control strategies in areas like Jakarta. Collaboration among government, communities, and various stakeholders is needed to implement mangrove planting programs for the sustainability of coastal environments and the well-being of communities.